Novēlējumu sintaktiskie varianti mutvārdu saziņā - Lauze, Linda (Baltistica, 2012)
SYNTACTIC VARIANTS OF WISHES IN SPOKEN COMMUNICATION Summary To this day the structural formation of wishes in Latvian has been described in the chapter “Optative Sentences” of books on Latvian syntax in which examples were mainly taken from written texts. The present paper focuses on the analysis of spoken utterances from everyday speech as well as from telephone conversations recorded from audiovisual mass media on different social occasions. Special attention is paid to the fact that a typical wish with a noun in the accusative case in its centre coexists with its syntactic variant in which the addressee in the dative case is added. At first sight, it seems to be a case of syntactic interference. But if one compares the mentioned syntactic variants to verbal utterances with a completely implemented structural model of the simple sentence, they should be regarded as utterances with the syntactical zero form of the predicate. The author ends the article with the analysis of structural formation of wishes with the particle lai. According to the author, the existence of the syntactic zero form testifies to the possibility of treating these utterances as a partly implemented structural model of the simple sentence. The present research encourages a discussion about the classification of optative sentences according to their morphological type.